k-Watson-Crick Petri net controlled grammars - Mohamad Jan, Nurhidaya; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (CESER Publications, 2015)
A Watson-Crick Petri net is an extension of a Watson-Crick automaton where the control by finite automaton is replaced by a Petri net. By adapting the different types of Petri nets, various variants of Watson-Crick Petri nets and Watson-Crick Petri net controlled grammars such as reverse Watson-Crick Petri net and many more can be defined. In this paper, a modelling of k-Watson-Crick Petri net controlled grammars is introduced.